Development and characterization of PVC-based membranes embedded with magnetic silica core-shell composites for enhanced oil-water separation - Rana H.M. EL Hady; Gheith; Mostafa M.H. Khalil; Mahmoud F. Mubarak (Desalination and Water Treatment)
A novel polyvinyl chloride (PVC)--based membrane incorporating magnetic silica core-shell nanoparticles (CoFe2O4@SiO2) was developed for efficient oil-water separation. The CoFe2O4core enhances magnetic functionality, while the SiO2 shell improves hydrophilicity and nanoparticle dispersion. Characterization techniques confirmed structural integrity and uniform distribution. Performance evaluation demonstrated over 97 % oil rejection for emulsions up to 1200 ppm at 6 bar, with a 270 L/m²·h permeation flux and strong antifouling properties over multiple cycles. Enhanced mechanical stability was also observed. These findings highlight the potential of CoFe2O4@SiO2-integrated PVC membranes for advanced wastewater treatment and industrial oil separation applications.